PENGEMBANGAN KARIR APARATUR SIPIL NEGARA DI KANTOR PERTANAHAN KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Anggara, Bagus Budi (Katalogis, 2018)
This Research Target is to know and analyse the Implementation ofÂ Career Development of Aparatur State Civil in Office at Land Affair of Sigi Regency. This Research Type is research qualitative with the informan selected by the seven of people. Data collecting use the perception technique, interview and documentation. Technique analyse the data used by that is (1) Data collecting ( 2) Data Discount ( 3) Data Presentation ( 4) Verification ( 5) Theory Conclusion used in this peneletian that is Opnion Hasibuan ( 2008) measuring career development by means ofÂ measure the Diklat, Achievementi ASN, Mutation And Promotion. Pursuant to result of research and analysis done/conducted by a researcher is hence concluded as follows: (1) Career Development of Aparatur State Civil inin Office at Land Affair of Sigi Regency seen from factor Diklat not yet maximal or not yet walked better (2) Career Development of Aparatur State Civil in Office at Land Affair of Sigi Regency seen from factor of Achievement ASN not yet maximal (3) Career Development of Aparatur of State Civil in Office at Land Affair of Sigi Regency seen from Mutation factor not yet maximal or not yet walked better and (4) Career Development of Aparatur State Civil in Office at Land Affair of Sigi Regency Sigi seen from Promotion factor not yet maximal or not yet walked better.